Rating the rankings: Assessing international rankings of public service performance - Hood, C; Dixon, R; Beeston, C (2008)
This paper documents the growth of international rankings of governance and public services and seeks to contribute to a second-generation approach to the analysis of this phenomenon. It does so primarily by setting out a method for ranking international ratings, building on and extending earlier work by other scholars, and applies that method to 14 international rankings of governance and public services, to explore the scope and limits of the approach. The final section argues that the development of such a method could form the basis for benchmarking international rankings as they develop in the future.